(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2018)
The experimental studies results of reinforced concrete elements with sheet reinforcement load bearing capacity are presented. The drawing of experimental designs is shown. The bearing capacity dependence graphs of the tested steel-reinforced concrete samples with sheet reinforcement on the height of the element and dependence graphs of tested steel-reinforced concrete samples with sheet reinforcement carrying capacity on the applied eccentricity are constructed. The photo shows the destruction character of experimental steel-concrete samples with sheet reinforcement depending on their height. The general schedule of bearing capacity dependence on the height of the element and the eccentricity of the applied load is constructed.